The human animal : personal identity without psychology - Olson, Eric T. (Eric Todd), 1963- (Philosophy of mind series., 1997)
What does it take for you to persist from one time to another? What sorts of changes could you survive, and what would bring your existence to an end? What makes it the case that some past or future being, rather than another, is you? So begins Eric Olson's pathbreaking new book, The Human Animal: Personal Identity Without Psychology. You and I are biological organisms, he claims; and no psychological relation is either necessary or sufficient for an organism to persist through time. Conceiving of personal identity in terms of life-sustaining processes rather than bodily continuity distinguishes Olson's position from that of most other opponents of psychological theories. And only a biological account of our identity, he argues, can accommodate the apparent facts that we are animals, and that each of us began to exist as a microscopic embryo with no psychological features at all. Surprisingly, a biological approach turns out to be consistent with the most popular arguments for a psychological account of personal identity, while avoiding metaphysical traps. And in an ironic twist, Olson shows that it is the psychological approach that fails to support the Lockean definition of "person" as (roughly) a rational, self-conscious moral agent, an attractive view that fits naturally with a biological account.